The Changes of P-fractions and Solubility of Phosphate Rock in Ultisol Treated by Organic Matter and Phosphate Rock - Sri Djuniwati; Budi Nugroho; Heru Bagus Pulunggono (UNIVERSITY OF LAMPUNG, 2012)
Phosphorus (P) is one of the essential elements for plant, however, its availability is mostly very low in acid soils. It is well documented that application of phosphate rock and organic matter are able to change the level of availability of P-form in acid soils. The objective of the research were to evaluate the changes of P-fractions ( resin-P, NaHCO3-Pi, and NaHCO3-Po) and phosphate rock dissolution which were induced by application of organic matter (Imperata cylindrica, Pueraria javanica, dan Colopogonium mucunoides) and phosphate rock in Utisol Lampung. The experiment was designed in a completely randomized design with three factors and three replications. The first factor was the types of organic matter (I. cylindrica, P. javanica, and C. mucunoides), the second factor was the rate of organic matter (0, 2.5, and 5%), and the third factor was the rate of phosphate rock (0, 40, and 80 mg P kg-1). The results showed that in the rate of 0 and 1% organic matter, the type of organic matter did not affect P-fraction of NaHCO3-Pi, but in the rate of 2.5 and 5%, NaHCO3-Pi due to application of P. javanica, and C. mucunoides higher than due to application of I. cylindrica. However, the increasing rate of organic matter increased NaHCO3-Pi. Then, P-fraction of Resin-Pi was affected by the type of organic matter, the rate of organic matter, and the rate of phosphate rock, respectively. P-fraction of resin-Pi due to application of P. javanica, and C. mucunoides was higher than due to application of I. cylindrica, but the effect of P. javanica, and C. mucunoides was not different. Increasing the rate of organic matter and phosphate rock increased P-fraction of resin-Pi and NaHCO3-Pi, but P-fraction of NaHCO3-Po was not affected by all treatments. Meanwhile, dissolution of phosphate rock was affected by the kind of organic matter and soil reaction. In the rate of 5% organic matter, dissolution of phosphate rock by application of I. cylindrica (70%) was higher than P. javanica (26.6%), and C. mucunoides (33.5%), but in the rate of 1%, the effect of I. cylindrica , P. javanica, and C. mucunoides were not different.Keywords: C. mucunoides; I. cylindrica; P. javanica; phosphate rock; P-fractions[How to Cite: Djuniwati S, B Nugroho, and HB Pulunggono. 2012. The Changes of P-fractions and Solubility of Phosphate Rock in Ultisol Treated by Organic Matter and Phosphate Rock. J Trop Soils, 17: 203-210. doi: 10.5400/jts.2012.17.3.203][Permalink/DOI: www.dx.doi.org/10.5400/jts.2012.17.3.203]